The Communist Manifesto, 170 Years Later - Amin, Samir (Sociološki pregled, 2018)
No text written in the mid-nineteenth century has held the road until today as well as the Communist Manifesto of 1848. Even today entire paragraphs of the text correspond to the contemporary reality even better than in 1848. Starting from the premises which were hardly visible in the era, Marx and Engels drew the conclusions which the deployment of 170 years of history fully consolidated. In this article I will give further enlightening examples.